Biotechniques for air pollution abatement and odour control policies : proceedings of an international symposium, Maastricht, the Netherlands, 27-29 October, 1991 - Dragt, A. J.; Ham, J. van.; ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 1992)
The increasing concern for odour abatement, and more generally for reduction of air pollution, has caused a rapid growth in the development of air pollution control techniques, several of which are based on biological degradation of the polluting compounds. This book presents a state-of-the-art overview of recent developments in biological techniques for air pollution control. It describes in detail processes for the prevention of odour nuisances and reduction of odour emissions. It also deals with process design and construction of equipment as well as with odour policy measurements at an international level.
Front Cover; Biotechniques for Air Pollution Abatement and Odour Control Policies; Copyrigt Page; Contents; PART I: OPENING SESSION; PART II: PROCESS DESIGN and CONSTRUCTION for BIOTECHNIQUES; PART III: NEW DEVELOPMENTS for IMPROVING BIOTECHNIQUES; PART IV: BIOTECHNIQUES for ODOUR ABATEMENT: APPLICATIONS in INDUSTRY; PART V: MIXED SOLUTIONS for AIR POLLUTION ABATEMENT in INDUSTRY; PART VI: INTENSIVE STOCK BREEDING: PRACTICE of ODOUR ABATEMENT; PART VII: REMOVAL of SPECIFIC COMPONENTS in INDUSTRIAL SITUATIONS; PART VIII: ODOUR CONTROL POLICIES; PART IX: OLFACTOMETRY; Author Index.
"Society for Clean Air in the Netherlands, Vereniging Lucht."
Includes bibliographical references and indexes.
Print version record.
Elsevier
Keywords: Air quality management -- Congresses; Odor control -- Congresses; Bioremediation -- Congresses; TECHNOLOGY & ENGINEERING -- Environmental -- Pollution Control; Air quality management; Bioremediation; Odor control; Luchtverontreiniging; Biotechnologie; Milieutechniek; Electronic books